Burnout among nurses working in social welfare centers for the disabled - Lahana, Eleni; Papadopoulou, Konstantina; Roumeliotou, Olga; Tsounis, Andreas; Sarafis, Pavlos; Niakas, Dimitris (My University, 2017)
Background: In the healthcare sector, we often come across the burnout syndrome. It is an occupational syndrome which causes, physical and emotional exhaustion. More information is needed on the dangers of burnout and how often it occurs in healthcare. The purpose of this study was to investigate burnout and factors associated with the syndrome among nurses working with people that are mentally challenged. Methods: A cross-sectional survey was conducted, among 180 nurses working in public health centers for the disabled in multiple regions of Greece. A self-administered questionnaire with questions about socio-demographic and work-related characteristics was used, as well as the Maslach Burnout Inventory (MBI) for burnout assessment. Univariate and multivariate analyzes were performed. Results: The burnout dimensions of emotional exhaustion (Mean = 31.36) and depersonalization (Mean = 11.27) were at high levels while personal accomplishment was at low levels (Mean = 44.02). Female nurses had a higher personal accomplishment score (Mean = 44.82, p = 0.047) than men (Mean = 42.10, p = 0.047). Marital status, daily routine and relationships with supervisors were significantly related with emotional exhaustion and personal accomplishment and professional experience with higher levels of emotional exhaustion and depersonalization. Reason for professional selection was an independent predictor for depersonalization and personal accomplishment, with those that have selected the nursing profession randomly or because of the fear of unemployment having higher scores. Moderate relationships with colleagues was an independent predictor for all burnout dimensions. Conclusions: Nurses working in services for people with intellectual disabilities in Greece show increased burnout levels. Burnout can be prevented by offering more opportunities for professional advancement and education, new ways to provide supervisor support, provide incentives for nurses to initiate or participate in innovative programs. Specific training on conflict resolution, collaboration, reinforcement and stress coping techniques must be implemented.
Keywords: Annexes disabled; Nurses; Burnout; MBI; Intellectual disabilities